Monitoring oxygen levels of windu shrimp pond water using dissolved oxygen sensor based on wemos D1 R1 - Djainuddin, Djainuddin; Fattah, Farniwati; Asis, Muhammad Arfah; Satra, Ramdan; Fattah, Muhammad Hattah; Adam Ali Abdalla, Modawy (Bulletin of Social Informatics Theory and Application, 2024)
This research implements an oxygen monitoring system in tiger shrimp ponds using a Dissolved Oxygen (DO) sensor based on Wemos D1 R1 with an Internet of Things (IoT) approach. Tiger shrimp ponds, as aquaculture centers, require regular monitoring of water quality. The system uses DO sensors in the water, processed by Wemos D1 R1, and the data is sent to Firebase Cloud for storage. A web application serves as the user interface to monitor and analyze the data. The results of the research in Pandawa 1000 tiger shrimp pond, Lanrisang Village, Pinrang, showed the positive impact of IoT technology on pond management. The selection of the Wemos D1 R1 and the use of the Dissolved Oxygen Sensor enabled accurate and efficient measurement of oxygen levels, overcoming the shortcomings of previous research, especially the integration of the sensor directly into Firebase for real-time data storage and delivery. This development improves connectivity and real-time monitoring capabilities, crucial aspects in ensuring optimal pond water quality.